Asymptotically Linear Solutions for Some Linear Fractional Differential Equations. (25th November 2010) - Băleanu, Dumitru; Mustafa, Octavian G.; Agarwal, Ravi P.
Abstract : We establish here that under some simple restrictions on the functional coefficienta ( t ) the fractional differential equationD 0 t α [ t x ′ − x + x ( 0 ) ] + a ( t ) x = 0,    t > 0, has a solution expressible asc t + d + o ( 1 ) fort → + ∞, whereD 0 t α designates the Riemann-Liouville derivative of orderα ∈ ( 0, 1 ) andc, d ∈ ℝ .